A method for solving the transportation problem. Issue 5 (3rd September 2018) - Sadeghi, Javad
Abstract: The transportation problem as a major problem in linear programming problems is important. To solve the transportation problem we need to find a feasible solution. The feasible solution of the transportation problem can be obtained by using the least cost, Vogel or other methods. After obtaining feasible solutions, we use the existing methods such as multiples method or the method of stepping stones to achieve the optimal solution. In These methods, we need to find a route in the transportation table. It is relatively difficult to find a route. Here, we propose a new method that does not require finding a route and is easier than previous methods. At the end, this method compared with previous methods.